Kinematic analysis of the drag flick in field hockey - Ibrahim, R.; Faber, G. S.; Kingma, I.; van Dieën, J. H. (Sports Biomechanics, 2017)
Attaining high speed of the stick head and consequently of the ball is essential for successful performance of the drag flick in field hockey, but the coordination pattern used to maximise stick head speed is unknown. The kinematics of the drag flick was studied in ten elite hockey players who performed twenty shots each towards a target located 1.5m high. A 150Hz active marker motion analysis system was used, alongside two force plates to detect foot touchdown. Angular velocity and contribution to stick endpoint speed of upper body joints were analysed. Repeated measures ANOVA was used to compare timing of onset and peak angular velocities between joints. Participants used a kinematic pattern that was close to a proximal-to-distal sequence. Trunk axial rotation and lateral rotation towards the target, right wrist flexion and left wrist extension were the main contributors to stick endpoint speed. Coaches should emphasise trunk rotations and wrist flexion and extension movements for maximising stick head speed. Given the high level of the participants in this study, the coordination of joints motions, as reported here, can serve as a guideline for drag flick training. ABSTRACT FROM AUTHOR